Java Programming for Absolute Beginners - Safari eBooks ([Place of publication not identified] : Stone River eLearning, 2014)
"Perfect for beginners, the Learn Java Programming From Scratch Online Course takes you from a Java beginner to an expert in no time at all. Java programming is used in various applications such as Android mobile app development and software development. Having a firm understanding of Java programming is essential for most developers. This course is perfect for everyone from those who have never programmed before, to programmers who need a brush up on Java or did not learn Java in the past."--Resource description page.
Title from resource description page (viewed December 9, 2014)
Presenter, Stone River eLearning.
Keywords: Java (Computer program language); Electronic books